Uncovering the Genetic Landscape of Pediatric Hearing Loss Along the Texas–Mexico Border - Desiree Lanehart; Michelle Gray; Roberta Sierra; Camille Maldonado; Daniel Brooks; Hongzheng Dai; Aaly Rahimtoola; Sandy Magallan; Sarah Rodriguez; Jose Gamez; Pattie Rosenlund; Surya N. Mulukutla; et al. (Clinical Genetics, 2026)
ABSTRACT Children in Health Professional Shortage Areas (HPSAs), including the US border regions, experience delays in the diagnosis of hereditary hearing loss (HL), driven primarily by limited access to specialized genetic services. Although approximately 60% of congenital HL has a genetic etiology, many affected children in these communities remain undiagnosed, delaying timely intervention. Project GIVE is an NIH‐funded virtual genomics program that expands access to genome sequencing (GS) for children with undiagnosed multisystemic conditions along the Texas–Mexico border in the Rio Grande Valley (RGV) and El Paso regions of Texas, USA. Children (0–18 years) with suspected rare diseases were referred by regional healthcare professionals through a virtual portal, Consultagene, and underwent comprehensive virtual clinical genetics evaluation and trio GS. Among 23 Hispanic/Latino children evaluated for HL, 16 (~70%) received a molecular diagnosis. Of these, 56% had changes to medical management. Our findings demonstrate that high diagnostic yield for pediatric HL can be achieved in under‐resourced populations when genomic testing barriers are addressed. As targeted therapies for hereditary HL emerge, broader implementation of comprehensive genetic testing in HPSAs is crucial to ensure timely medical interventions.